High volume-rate echocardiography for simultaneous imaging of electromechanical activation and cardiac strain of the whole heart in a single heartbeat in humans. - Julien Grondin; Hannah J Schleifer; Rachel Weber; Changhee Lee; Melina Tourni; Elisa E Konofagou (PLoS ONE)
Background Imaging both electrical and mechanical cardiac function can better characterize cardiac disease and improve patient care. Currently, there is no noninvasive technique that can simultaneously image both electrical and mechanical function of the whole heart at the point of care. Here, our aim is to demonstrate that high volume-rate echocardiography can simultaneously map cardiac electromechanical activation and end-systolic cardiac strain of the whole heart in a single heartbeat. Method A 32x32 ultrasound matrix array connected to four synchronized ultrasound scanners were used for transthoracic high volume-rate imaging (840 volumes/s) in sixteen young volunteers (28.1±4.2 y.o.). An electromechanical activation map of the whole heart and volumetric end-systolic atrial and ventricular strain images were obtained. Results The whole heart activation sequence was found to be consistent across volunteers and in agreement with previously reported normal electrical activation sequences. The mean electromechanical activation time was 72.6±15.2 ms in the atria, 132.4±19.7 ms in the ventricles and 154.5±19.6 ms in the whole heart. Volumetric right and left atrial as well as right and left ventricular strains were also consistent across all volunteers, with a mean end-systolic global longitudinal strain of 26.8±6.5% in the atria and -16.6±3.4% in the ventricles. Conclusions This initial feasibility study demonstrates that noninvasive high-volume rate imaging of the heart in a single heartbeat is feasible and can provide electromechanical activation and systolic strains simultaneously in all four cardiac chambers. This technique can be further developed and used at the point of care to assist for screening, diagnosis, therapy guidance and follow-up of heart disease patients.